Perlindungan Hukum terhadap Perawat di Masa Pandemi Covid-19 - Likelly Claudia; Paula Gabriella Sinaga; Emir Syarif Pakpahan (Mahesa Research Center, 2022)
This article aims to find out the legal protection for nurses during the Covid-19 pandemic. The problem is focused on efforts to protect the safety of nurses in handling Covid-19 patients at the Sidikalang Hospital and the legal protection given to patient nurses in handling Covid-19 patients at the Sidikalang Hospital and the factors that hinder legal protection and work safety for nurses in handling patients. Covid-19 at Sidikalang Hospital. In order to approach this problem, a juridical-empirical theoretical reference is used. The data were collected through interviews. And previous research and analyzed qualitatively. This study concludes that knowing the efforts of work safety, legal protection, and what factors hinder legal protection and work safety, the method applied is in the form of empirical juridical which studies the applicable legal provisions and what has occurred in social life. Based on this study, it was concluded that nursing staff, namely nurses, had received legal protection for work safety, which had been carried out properly in accordance with what was mandated in the legislation and provided incentive rights for nurses who handled COVID-19 patients.